Phage Therapy: Beyond Antibacterial Action - Górski, Andrzej; Jończyk-Matysiak, Ewa; Międzybrodzki, Ryszard; Weber-Dąbrowska, Beata; Łusiak-Szelachowska, Marzanna; Bagińska, Natalia; Borysowski, Jan; Łobocka, Małgorzata B.; Węgrzyn, Alicja; Węgrzyn, Grzegorz (Frontiers in Medicine, 2018)
Until recently, phages were considered as mere “bacteria eaters” with potential for use in combating antimicrobial resistance. The real value of phage therapy assessed according to the standards of evidence-based medicine awaits confirmation by clinical trials. However, the progress in research on phage biology has shed more light on the significance of phages. Accumulating data indicate that phages may also interact with eukaryotic cells. How such interactions could be translated into advances in medicine (especially novel means of therapy) is discussed herein.